A Context-Aware System Infrastructure for Monitoring Activities of Daily Living in Smart Home. (15th March 2016) - Ni, Qin; García Hernando, Ana Belén; Pau de la Cruz, Iván
Abstract : We propose a three-layered context-aware architecture for monitoring activities of daily life in smart home. This architecture provides for the inclusion of functionalities that range from low-level data collection to high-level context knowledge extraction. We have also devised an upper-level ontology to model the context in which the activities take place. This enables having a common activity-related context representation, on which to infer and share knowledge. Furthermore, we have begun to implement a platform that realizes our architecture and ontology, making use of Microsoft's Lab of Things (LoT) platform, being the preliminary results on this task also described in the paper.